Factors driving the bioavailability of particulate organic matter in the Ross Sea (Antarctica) during summer - Misic, Cristina; Bolinesi, Francesco; Castellano, Michela; Olivari, Enrico; Povero, Paolo; Fusco, Giannetta; Saggiomo, Maria; Mangoni, Olga (Hydrobiologia, 2024)
The biochemical composition and bioavailability of particulate organic matter (POM) were studied in relation to abiotic (water column stratification, macronutrient concentrations) and biotic factors (phytoplankton biomass and functional groups) in the open Ross Sea and coastal area of Terra Nova Bay, Antarctica, during the austral summer 2017. The presence of different sub-systems was highlighted by spatial and temporal variations of all the considered variables, characterised by higher concentrations of particulate organic carbon and nitrogen in Terra Nova Bay, where diatoms dominated, while in the open Ross Sea was higher the contribution of haptophytes (Phaeocystis antarctica Karsten, 1905). The southernmost Ross Sea was characterised by significantly higher concentrations of carbohydrates in the entire water column. High lipid contribution and low photosynthetic activity indicated aged POM, suggesting that POM was composed mainly by the remnants of previous haptophytes production. The higher lability of the carbohydrates indicated that an increase of haptophytes in the area could alter the biogeochemical C cycle, reducing the storage of refractory carbon in the depths, and favouring the transfer and respiration of C in the trophic web, with a decrease of export rate in the Ross Sea.